Na+ dependent acid-base transporters in the choroid plexus; insights from slc4 and slc9 gene deletion studies - Christensen, Henriette L.; Nguyen, An T.; Pedersen, Fredrik D.; Damkier, Helle H. (Frontiers in Physiology, 2013)
The choroid plexus epithelium (CPE) is located in the ventricular system of the brain, where it secretes the majority of the cerebrospinal fluid (CSF) that fills the ventricular system and surrounds the central nervous system. The CPE is a highly vascularized single layer of cuboidal cells with an unsurpassed transepithelial water and solute transport rate. Several members of the slc4a family of bicarbonate transporters are expressed in the CPE. In the basolateral membrane the electroneutral Na+ dependent Cl-/HCO3- exchanger, NCBE (slc4a10) is expressed. In the luminal membrane, the electrogenic Na+:HCO3- cotransporter, NBCe2 (slc4a5) is expressed. The electroneutral Na+:HCO3- cotransporter, NBCn1 (slc4a7), has been located in both membranes. In addition to the bicarbonate transporters, the Na+/H+ exchanger, NHE1 (slc9a1), is located in the luminal membrane of the CPE. Genetically modified mice targeting slc4a2, slc4a5, Slc4a7, Slc4a10, and Slc9a1 have been generated. Deletion of slc4a5, 7 or 10, or slc9a1 has numerous impacts on CP function and structure in these mice. Removal of the transporters affects brain ventricle size (slc4a5 and slc4a10) and intracellular pH regulation (slc4a7 and slc4a10). In some instances, removal of the proteins from the CPE (slc4a5, 7 and 10) causes changes in abundance and localization of non-target transporters known to be involved in pH regulation and CSF secretion. The focus of this review is to combine the insights gathered from these knockout mice to highlight the impact of slc4 gene deletion on the CSF production and intracellular pH regulation resulting from the deletion of slc4a5, 7 and 10, and slc9a1. Furthermore, the review contains a comparison of the described human mutations of these genes to the findings in the knockout studies. Finally, the future perspective of utilizing these proteins as potential targets for the treatment of CSF disorders will be discussed.